Method for identifying feed-drive system dynamic properties using a motor current. (November 2016) - Liu, Xing; Mao, Xinyong; Liu, Hongqi; Li, Bin; Guan, Chuangfu; Zhang, Zisheng; Luo, Bo; Peng, Fangyu
Abstract: The dynamics of a machine tool ball screw is an important topic in high-precision machining. Capturing the axial and torsional dynamics of the ball screw has an important guiding significance to the stable processing of the machine tool. The traditional methods mainly involve a mounted sensor or direct embedment into the structure and hybrid finite element methods (FEMs), which are inconvenient. The FEM accuracy is limited by the accuracy of the model. This paper reports that feed-drive system vibration is excited by the interactive impact of a screw, ball, and nut, whose interaction is the core of the feed-drive system dynamics. Under the action of current, the ball screw serves as the transmission component of the executive component to control the working condition of the sliding table. This paper proposes a new method that uses the inertia force sequence caused by random idle running of the sliding table to identify the natural frequency of a feed-drive system based on the feed motor current response. First, the corresponding relationship between the current and the vibration of the feed-drive system is studied. The accuracy of the new method based on the current response is analysed by the experiment, which is performed to identify the natural frequency of the feed-drive system. Then, the incentive region is changed to study the identification effect under different interactive impact conditions, where the contact condition of the ball screw is different. Highlights: Based on the motor current to identify the natural frequency of feed-drive system. Studied the relationship of motor current and vibration of the feed-drive system. Analysed the accuracy of the new method by the experiment.